Management of Infected Non Union Tibial Shaft by Ilizarov Method (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To asses the out come of the management of infected non union of tibial shaft by Ilizarov method.Patients and Methods: This prospective study was conducted at department of orthopedic CMC Larkana and GMMMC Sukkur from March 2008 to February 2011. Forty five patients with infected non-union of tibia with or without shortening and bone loss were included.Results: 45 Patients were included in this study. Out of 45 patients, 27 were male and 18 were females. The average follow up period was 18 months. No patients have lost follow-up. No mortality was observed in current study. The over all success rate was 95%.Conclusion: Management of infected non union of tibia is one of the most perplexing dilemma of orthopaedic surgery. Where as the traditional methods of treatment of infected non-union involve extensive operative exposure with repeated debridents, prolong use of local and parenteral antibiotics, bone grafting and long period of immobilization. Ilizarov technique is minimally invasive, and apart from obtaining union with distraction/compression osteogenesis. This method has added advantage of immediate mobilization and early weight bearing. Key Words: Infected non-union, Tibia, Ilizarov method